Post-manifesto polygamy: the 1899-1904 correspondence of Helen, Owen, and Avery Woodruff - Snyder, Lu Ann Faylor, editor; Snyder, Phillip A., editor; Utah State University Press, publisher (Colorado State University. Libraries, 2009)
These letters among two women and their husband offer a rare look into the personal dynamics of an LDS polygamous relationship. Abraham Owen Woodruff was a young polygamous Mormon apostle, and the son of LDS President Wilford Woodruff, who is remembered for the Woodruff Manifesto, a divinely-inspired call for the termination of plural marriage. The Woodruff Manifesto eased a systematic federal judicial assault on Mormons and made Utah statehood possible. It did not end polygamy in the church. Some leaders continued to encourage and perform such marriages. Owen Woodruff, himself married to Helen May Winters, contracted a secretive second marriage to Avery Clark. Pressure on the LDS church revived with hearings regarding Reed Smoot's seat in the U.S. Senate. After church president Joseph F. Smith issued the so-called Second Manifesto in 1904, polygamy and its more prominent advocates were mostly expunged from mainstream Mormonism. Owen Woodruff had often been "on the underground," moving frequently, traveling under secret identities, and using code names in his letters to his wives, while still carrying out his administrative duties, which, in particular, involved supervision of the nascent Mormon colonies in the Big Horn Basin of Wyoming. He was never excommunicated, as some of his apostolic colleagues were. Both he and his first wife, Helen, while living with Avery in Mexico and preparing for a mission to Germany, contracted smallpox and died suddenly in 1904. Avery later returned to Utah with her children along with those of Helen and Owen.--Provided by publisher.
Letter 1, Helen to Owen, July 17 -- Letter 2, Helen to Owen, August 14 -- Avery's autobiography and recollections: excerpt A, 1900 -- Letter 3, Avery to Owen, October 25 -- Letter 4, Helen to Owen, November 4 -- Letter 5, Avery to Owen, November 7 -- Letter 6, Helen to Owen, November 10 -- Letter 7, Helen to Owen, November 10 -- Letter 8, Helen to Owen, November 11 -- Letter 9, Helen to Owen, November 12 -- Letter 10, Avery to Owen, November 17 -- Letter 11, Helen to Owen, November 19 -- Letter 12, Helen to Owen, November 21 -- Letter 13, Helen to Owen, November 23 -- Letter 14, Helen to Owen, December 2 -- Letter 15, Helen to Owen, December 4 -- Letter 16, Avery to Owen, December 8 -- Letter 17, Avery to Owen and Helen, December 16 -- Avery's autobiography and recollections: excerpt B, 1901 -- Letter 18, Avery to Owen, January 12 -- Letter 19, Avery to Owen, January 27 -- Letter 20, Avery to Owen and Helen, February 16 -- Letter 21, Avery to Owen, march 12 -- Letter 22, Helen to Owen, March 17 -- Letter 23, Helen to Owen, March 18 -- Letter 24, Helen to Owen, March 19 -- Letter 25, Avery to Helen, May 16 -- Letter 26, Avery to Owen and Helen, May 30 -- Letter 27, Avery to Owen and Helen, June 14 -- Letter 28, Owen to Avery, November 15 -- Letter 29, Helen to Avery, November 24, 1902 -- Letter 30, Owen to Avery, January 14 -- Letter 31, Owen to Helen, January 17 -- Letter 32, Owen to Helen, January 21 -- Letter 33, Owen to Avery, February 29 -- Letter 34, Owen to Avery, March 17 -- Letter 35, Owen to Avery, May 1 -- Letter 36, Owen to Avery, June 7 -- Letter 37, Owen to Avery, July 4 -- Letter 38, Owen to Helen, July 12 -- Letter 39, Helen to Owen, July 20 -- Letter 40, Owen to Avery, July 25 -- Letter 41, Owen to Helen, August 5 -- Letter 42, Owen to Avery, August 8 -- Letter 43, Owen to Avery, August 16 -- Letter 44, Owen to Avery, August 22 -- Letter 45, Owen to Helen, August 25 -- Letter 46, Owen to Avery, September 30 -- Letter 47, Owen to Avery, October 18 -- Letter 48, Owen to Avery, October 26 -- Letter 49, Owen to Avery, November 9 -- Letter 50, Owen to Avery, November 21,1903 -- Letter 51, Owen to Avery, January 19 -- Letter 52, Owen to Avery, January 29 -- Letter 53, Helen to Owen, February 4 -- Letter 54, Helen to Owen, March 5 -- Letter 55, Owen to Avery, May 2 -- Letter 56, Owen to Avery, June 29 -- Letter 57, Owen to Avery, September 2 -- Letter 58, Helen to Avery, October 4 -- Letter 59, Helen to Owen, October 27 -- Letter 60, Helen to Owen, November 1 -- Letter 61, Helen to Owen, November 11 -- Letter 62, Owen to Avery, November 14 -- Letter 63, Avery to Helen, December 22 -- Avery's autobiography and recollections: excerpt C, 1904 and aftermath -- Letter 64, Owen to Avery, January 1 -- Letter 65, Owen to Avery, January 5 -- Letter 66, Owen to Avery, January 16 -- Letter 67, Owen to Avery, January 22 -- Letter 68, Helen to Owen, February 4 -- Letter 69, Helen to Owen, February 9 -- Letter 70, Helen to Owen, February 12 -- Letter 71, Helen to Owen, February 19 -- Letter 72, Helen to Owen, February 20 -- Letter 73, Helen to Owen, February 24 -- Letter 74, Helen to Owen, March 1 -- Letter 75, Helen to Owen, March 6 -- Letter 76, Helen to Owen, March 8 -- Letter 77, Owen to Avery, March 8 -- Letter 78, Owen to Avery, March -- Letter 79, Helen to Owen, March 12 -- Letter 80, Helen to Owen, March 16 -- Letter 81, Owen to Avery, May 7 -- Letter 82, Owen to Avery, May 18 -- Letter 83, Owen to Avery, May 20 -- Letter 84, Avery to Owen, May 30 -- Letter 85, Avery to Owen, June 1 -- Avery's autobiography and recollections: excerpt D, Alonzo I. Taylor's journal -- Kate Spilsbury's recollections -- Emma Woodruff letters to Avery -- Woodruff circle of family and friends.
Keywords: Polygamy -- Religious aspects -- Church of Jesus Christ of Latter-day Saints; Polygamy -- Religious aspects -- Mormon Church; Woodruff, Abraham Owen, 1872-1904 -- Correspondence; Woodruff, Helen May Winters, 1873-1904 -- Correspondence; Lambert, Eliza Avery Clark Woodruff, 1882-1953 -- Correspondence